Exploring strategies for planned urban cluster development in South Asia. - Jha, Shikha (South Asia working papers.)
It examines the concept of urban clusters and explores its application in South Asia. Drawing lessons from international case studies, it highlights the advantages of clustered urbanization. It identifies Delhi, Dhaka, and Mumbai as mature clusters; and Ahmedabad, Bengaluru, Chennai, Colombo, Kathmandu, and Pune as emerging clusters. It discusses evolving development priorities for these cities with regard to economic development, urban infrastructure and services, governance and citizen engagement, finance, and environmental protection and resilience. It also explores strategies for financing cluster development. Planned development of these clusters has the potential to drive regional economic growth.